Gene duplication, horizontal gene transfer, and trait trade-offs drive evolution of postfire resource acquisition in pyrophilous fungi - Ehsan Sari; Dylan J. Enright; Maria E. Ordoñez; Steven D. Allison; Peter M. Homyak; Michael J. Wilkins; Sydney I. Glassman (Proceedings of the National Academy of Sciences, 2026)
Wildfires significantly alter soil carbon (C) and nitrogen (N), reducing microbial richness and biomass, while selecting for “fire-loving” pyrophilous microbes that drive postfire nutrient cycling. However, the genomic strategies and functional trade-offs (balancing gains in one trait with costs in another) underlying the traits that enable pyrophilous microbes to survive and thrive postfire are virtually unknown. We hypothesized that pyrophilous fungi employ specialized genomic adaptations for C and N cycling, with evolutionary trade-offs between traits governing aromatic C degradation, N acquisition pathways, and rapid growth. To test these hypotheses, we performed complementary comparative genomics, transcriptomics after pyrogenic organic matter amendment, and growth rate bioassays for 18 pyrophilous fungi from five Ascomycota (Eurotiales, Pleosporales, Sordariales, Coniochaetales, and Pezizales) and three Basidiomycota (Agaricales, Holtermanniales, and Geminibasidiales) orders isolated from burned soils. We found a dramatic trait trade-off between fast growth and number of genes responsible for aromatic C degradation, implying burned environments select for metabolically costly genes despite their evolutionary cost. We used the comparative genomics framework to evaluate genomic signatures of evolution and found that either gene duplication and somatic mutation, or recombination via sexual reproduction, were the primary drivers of fungal genomic variation in aromatic C degradation and N acquisition genes. Finally, we identified cross-kingdom bacterial to fungal horizontal gene transfer (HGT) as a secondary strategy producing novel aromatic C degradation genes. Overall, we found that trait trade-offs and genome evolutionary strategies are key drivers that may predict the persistence and contribution of pyrophilous fungi to global C and N cycling.